1997
DOI: 10.1108/01443579710171190
|View full text |Cite
|
Sign up to set email alerts
|

An international study of quality improvement approach and firm performance

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
167
2
14

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 246 publications
(198 citation statements)
references
References 20 publications
15
167
2
14
Order By: Relevance
“…In particular, every inefficacious process instance can be viewed as a quality issue in the business process. Note that the overall effect of quality management on cost and firm performance has been well recognized and empirically demonstrated [28]. This option is particularly interesting since associated measures can often be implemented with limited investments.…”
Section: Process Improvement Objectives (Pios)mentioning
confidence: 99%
“…In particular, every inefficacious process instance can be viewed as a quality issue in the business process. Note that the overall effect of quality management on cost and firm performance has been well recognized and empirically demonstrated [28]. This option is particularly interesting since associated measures can often be implemented with limited investments.…”
Section: Process Improvement Objectives (Pios)mentioning
confidence: 99%
“…Escrig-Tena (2004) recupera um conjunto de trabalhos -Mann e Kehoe (1994), Powell (1995), Larson e Sinha (1995), Adam et al, (1997), Lemak e Reed (1997), Easton e Jarrell (1998), Dow et al, (1999), Terziovski e Samson (1999) e Zhang (2000 -que têm por objetivo avaliar empiricamente as evidências da infl uência do sistema de gestão pela qualidade sobre os resultados das empresas. Utilizando metodologias distintas, cada um dos trabalhos avalia a infl uência dos diferentes componentes da TQM sobre o resultado operacional (melhorias nos processos e nas relações com os funcionários, com clientes e fornecedores) e sobre o resultado fi nanceiro (participação no mercado, crescimento das vendas, lucratividade e rentabilidade).…”
Section: Sistema De Gestão Pela Qualidade E Sua Influência Sobre a Peunclassified
“…Powell (1995), Lemak e Reed (1997) e Easton e Jarrell (1998) se concentram nos efeitos sobre os resultados fi nan-ceiros, enquanto Larson e Sinha (1995) e Dow et al, (1999) priorizam os efeitos sobre os resultados operacionais. Os demais -Mann e Kehoe (1994), Adam et al, (1997), Terziovski e Samson (1999) de Larson e Sinha (1995), Easton e Jarrel (1998) e Terziovski e Samson (1999) (Escrig-Tena, 2004, p. 629).…”
Section: Sistema De Gestão Pela Qualidade E Sua Influência Sobre a Peunclassified
“…Adam (1994), Adam et al (1997) and Flynn et al (1995) have shown that TQM helps to improve intrinsic quality through reduced defect rates and better design. Also intrinsic quality (another latent variable in the model) has a positive effect on consumer perceptions of quality (Flynn et al, 1995), and that perceived quality has a positive effect on growth in market share Aaker, 1987, Phillips et al, 1983).…”
Section: H4 Tqm Is Positively Related To Market Share Growth Throughmentioning
confidence: 99%
“…However, these studies only considered relationships between TQM and company performance but not the contribution of individual TQM dimensions. Adam (1994), Adam et al (1997), Anderson et al (1995), Flynn et al (1995), Forker (1997), Ittner and Larcker (1997) and Powell (1995) have considered how different quality improvement practices are related to company performance. However, there is a lack of agreement in the findings and some results are contradictory with TQM theories, as shown in Table 1 below.…”
Section: Introductionmentioning
confidence: 99%